A congenital soft tissue Ewing sarcoma in a newborn patient - Mustafa Akçalı; Hacer Yapıcıoğlu; Eray Akay; Ferda Özlü; Banu Kozanoğlu; Kıvılcım Erdoğan; Gülfiliz Gönlüşen; Mehmet Satar (The Turkish Journal of Pediatrics)
Congenital Ewing sarcoma is extremely rare. Here we present a newborn baby born with a mass on the left shoulder. Immunohistochemical staining showed congenital Ewing sarcoma. Chemotherapy and then surgical operation were planned, however the patient died before initiation of chemotherapy on the 30th day of life.